Parental autonomy support and future-oriented coping among high school students: Serial mediation of future time perspective and meaning in life - Zeng, Lianping; Peng, Xia; Zeng, Xiaoye; Wang, Hui; Xiao, Shifei; Chen, Yan (Frontiers in Psychology, 2022)
Guided by the ecosystem theory, this study aimed to explore the association between parental autonomy support and future-oriented coping of high school students, as well as the mediating effects of future time perspective and meaning in life in this relationship. A total of 707 Chinese high school students were involved in a paper questionnaire survey and data analysis. It was found that (1) parental autonomy support was significantly positively related to future-oriented coping. (2) Mediation analyses demonstrated that parental autonomy support directly affects future-oriented coping; parental autonomy support indirectly affects future-oriented coping through separate mediation and serial mediation of future time perspective and meaning in life. These findings have important implications for the improvement of future-oriented coping abilities of high school students.